Carbon aerogel-based solid-phase microextraction coating for the analysis of organophosphorus pesticides. Issue 1 (8th December 2020) - Jõul, Piia; Vaher, Merike; Kuhtinskaja, Maria
Abstract : A carbon aerogel-coated SPME fiber is prepared, and the DI-SPME-GC-MS method is developed for the analysis of organophosphorus pesticides from environmental samples. Abstract : The current study is focused on the in situ synthesis of a carbon aerogel (CA)-based solid-phase microextraction (SPME) fiber coating on stainless steel wire and evaluation of the suitability of CAs as SPME coating materials for the analysis of selected organophosphorus pesticides (OPPs) contained in environmental samples. A CA-based coating was obtained by pyrolyzing organic aerogels, which were prepared by the sol–gel polymerization of formaldehyde and 5-methylresorcinol, an oil shale processing by-product. The results demonstrated, for the first time, the in situ synthesis of a CA-based SPME fiber coating on stainless steel wire and its suitability for the extraction and preconcentration of six OPPs. Main parameters affecting the extraction efficiency were investigated and optimized. The direct immersion (DI)-SPME procedure combined with gas chromatography-mass spectrometry (GC-MS) for the simultaneous analysis of selected OPPs was successfully applied to the efficient and sensitive determination of analytes of interest in environmental matrices of honey and natural water samples. The developed CA-coated SPME fiber showed good linearity ( R 2 = 0.981–0.994), low detection limits (0.11–0.83 μg L −1 ) and satisfactory single fiber and fiber-to-fiber reproducibilities (8.8–12.3%, n = 5 and 11.4–17.2%, n = 3). The performance of the CA-coating was compared with that of commercially available SPME fiber coatings.